Short- and intermediate-term mortality in women and men after surgical versus interventional revascularization and aortic valve replacement. (14th October 2021) - Fortmeier, V; Mueller, P; Potratz, M; Friedrichs, K P; Scholtz, S; Gummert, J; Rudolph, V; Bleiziffer, S; Rudolph, T K
Abstract: Background: Patients with isolated aortic valve stenosis (AS) at intermediate and even low-risk benefit from an interventional treatment with TAVI as compared to surgical aortic valve replacement. Whether patients with concomitant coronary artery disease have a better outcome with an interventional (PCI plus TAVI) or surgical (CABG plus SAVR) treatment strategy is still unclear. Purpose: To evaluate the differences in 30-days (short-term) and one-year (intermediate term) mortality in women and men with CAD and AS undergoing a surgical or catheter-based treatment. Methods: All patients were treated in Heart and Diabetes Center Bad Oeynhausen during 2016–2019. The surgical group contained 932 patients, the interventional cohort 360 patients as a result of setting a maximum time interval of 3 months between PCI and TAVR. CABG+SAVR and PCI+TAVR cohorts were compared by using a propensity score analysis including age, left ventricular function, EuroSCORE II and degree of CAD as matching parameters. After matching the total cohort, 406 patients could be obtained. The matched female cohort consisted of 114 patients, the matched male cohort of 284 patients. As a primary endpoint all-cause mortality was analyzed at 30 days and one year after the procedure. Furthermore, procedural and post-procedural outcome were analyzed. Results: The studied TAVI cohort was a low to intermediate risk population (EuroScore II of the total cohort: 3.82 [2.49–6.64] in CABG+SAVR vs 4.36 [2.59–7.12] in PCI+TAVR, p=0.38; women: 6.18 [3.43–8.6], p=0.279; men: 4.39 [2.83–8.82], p=0.279). There was no significant difference in 30-days mortality between the surgical and interventional group, regarding the total cohort (3.9% vs 2.5%; p=0.398). Whereas in the male cohort 30-days mortality was comparable between interventional and surgical treatment (2.1% vs 2.1%; p=1), in the female group the surgical treatment showed a trend towards higher mortality without reaching statistical significance (8.8% vs 3.5%; p=0.242). Additionally, one-year mortality did not differ in the three cohorts between CABG+SAVR and PCI+TAVR (total cohort: 11.3% vs 12.8%; p=0.648 women: 14% vs 10.5%; p=0.568; men: 11.3% vs 14.8%; p=0.378). The number of postprocedural permanent pacemaker implantations was statistically higher after TAVR plus PCI (total cohort: 7.4% vs 15.3%; p=0.012; women: 7% vs 19.3%; p=0.052; men: 8.5% vs 19%; p=0.01). Furthermore, a significantly longer length of hospital stay was reported for the surgical cohort (total cohort: 13 [11–17] vs 11 [9–15]; p=0; women: 14 [12–18] vs 12 [10.5–15.5]; p=0.019; men: 13 [11–15] vs 11 [9–15]; p=0). Conclusion: In patients with AS and CAD there is no significant difference in short and intermediate term mortality when comparing surgical or interventional treatment. Subsequently, an interventional approach might be a legitimate alternative to CABG+SAVR in these patients. FUNDunding Acknowledgement: Type of funding sources: None.